Life's too short eaudiobook - Jimenez, Abby (The Friend Zone, 2021)
THE INSTANT NEW YORK TIMES BESTSELLER "A hilarious, tender, and altogether life-affirming gem of a book." —Emily Henry, bestselling author of Beach Read A brilliant and touching romantic comedy about two polar opposites, one adorable dog, and living every day to its fullest. When Vanessa Price quit her job to pursue her dream of traveling the globe, she wasn't expecting to gain millions of YouTube followers who shared her joy of seizing every moment. For her, living each day to its fullest isn't just a motto. Her mother and sister never saw the age of 30, and Vanessa doesn't want to take anything for granted. But after her half sister suddenly leaves Vanessa in custody of her baby daughter, life goes from "daily adventure" to "next-level bad" (now with bonus baby vomit in hair). The last person Vanessa expects to show up offering help is the hot lawyer next door, Adrian Copeland. After all, she barely knows him. No one warned her that he was the Secret Baby Tamer or that she'd be spending a whole lot of time with him and his geriatric Chihuahua. Now she's feeling things she's vowed not to feel. Because the only thing worse than falling for Adrian is finding a little hope for a future she may never see. Minnesota Book Awards winner BookRiot, Top Books of 2021 Goodreads, Best of 2021 Romance Finalist She Reads, Best of 2021 Romance Winner